Mapeo y análisis de programas EdTech en América Latina y el Caribe - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
Este documento se elaboró ​​en respuesta a una solicitud de la Oficina Regional de UNICEF para América Latina y el Caribe al Servicio de Asistencia de EdTech Hub en octubre de 2021. El equipo de UNICEF solicitó una lista seleccionada de programas de EdTech en la región de América Latina y el Caribe (ALC) y un análisis de un conjunto de programas preseleccionados con la intención de explorar su potencial para la implementación y el impacto a escala. Este informe no pretende cubrir todos los programas EdTech innovadores en la región de ALC. Más bien, presenta una lista de programas EdTech prometedores y analiza su diseño e implementación con el fin de explorar su relevancia y potencial para lograr un impacto a gran escala. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7306712 ZenodoArchiveConcept: 7306711 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7306712 10.53832/edtechhub.0132 2405685:ACLTCQV2 2405685:XIIQ4FSE
Keywords: _r:AddedByZotZen

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7023230 ZenodoArchiveConcept: 7023229 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7023230 10.5281/zenodo.7038003 10.53832/edtechhub.0111 2405685:E2R8AXSA 2405685:SMH62I7W 2405685:VINQBTJ5
Keywords: _r:AddedByZotZen

Mother Language Day 2021 - Haßler, Björn; Castillejo, Alice; Marzotto, Mia; El-Serafy, Yomna; Khalayleh, Abdullah; Koomar, Saalim; Langa, Ancha; Nyilinkindi, Jacques; Saadeddin, Zeina; Tegha, Ghislaine; Villavicencio Peralta, Xuzel Ana (2021)
To celebrate International Mother Language Day 2021, Björn spoke with Alice Castillejo and Mia Marzotto at Translators without Borders. We talked about the importance of mother tongue-based education and the need to support speakers of marginalised languages. Research around the world shows that educational outcomes are worse for students studying in a second language. The use of an unfamiliar language is linked to high dropout rates and low academic achievement. We also know that 40% of children worldwide are not educated in a language they speak at home. We need to put aside our assumptions about what languages people speak and understand. For example, Portuguese is only one of many languages spoken in Mozambique. To really understand the richness of different languages, we need to collect, share, and visualise the real picture. Having done that, we can then apply this information. Do children who speak a particular language drop out early? We can then develop multilingual educational tools for learners and teachers based on improved data about relevant languages. We can also track educational outcomes by primary language, to ensure no learner is left behind. We can use language data to take action on three levels: children, teachers, and systems. With children, we can identify which language groups didn’t register for school, dropped out early, or consistently underperform. We can then adjust our communication and programming to meet their needs, leaving no one behind. We can also take action to support teachers. With language data, we can also take action on a system level. If over 40% of children are educated in a language they don’t speak at home, we need to know how this affects their education. Much as we did for gender, if we don’t gather the data on inequality, we cannot begin to address it. Collective gathering and sharing of language data can allow us to understand how to increase learning outcomes for speakers of marginalised languages and provide the support they need and deserve.
ZenodoArchiveID: 5651994 previousDOI: 10.5281/zenodo.4555228 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4555228 10.5281/zenodo.5651994 2339240:CME4837H 2405685:BSJEPIY4 2405685:ZQCX7TX3
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Mother Language Day 2021: Improving data on mother-tongue languages for better learning outcomes - Haßler, Björn; Castillejo, Alice; Marzotto, Mia; El-Serafy, Yomna; Khalayleh, Abdullah; Koomar, Saalim; Langa, Ancha; Nyilinkindi, Jacques; Saadeddin, Zeina; Tegha, Ghislaine; Villavicencio Peralta, Xuzel Ana (EdTech Hub, 2021)
To celebrate International Mother Language Day 2021, EdTech Hub’s Björn Haßler spoke with Alice Castillejo and Mia Marzotto of Translators without Borders. They talked about the importance of mother tongue-based education and the need to support speakers of marginalised languages. This blog post captures their conversation. “How do we know that speakers of marginalised languages are left behind?” Alice: Research…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707931 2405685:E65E8VY5
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH